A New, Morphologically Cryptic Species of Adenomera Closely Related to Adenomera araucaria from the Atlantic Forest of Southern Brazil (Anura, Leptodactylidae) - Carvalho, Thiago R. de [UNESP]; Cassini, Carla S.; Taucce, Pedro P. G. [UNESP]; Haddad, Celio F. B. [UNESP] (Soc Study Amphibians Reptiles, 2019)
We describe a new species of Adenomera from the Brazilian Atlantic Forest corresponding to one of the candidate species indicated in the published phylogeny of the genus (sp. R). The new species differs from all 18 congeners by the combination of small size, absence of toe discs, and the advertisement call composed of a single nonpulsed note with pronounced frequency upsweep. From the closest related and morphologically cryptic Adenomera araucaria, the new species is distinguished only by its nonpulsed advertisement call (multipulsed call in A. araucaria). The new species is distributed in the Serra do Tabuleiro mountain range and the Santa Catarina Island, as well as localities in between them in the eastern portion of the state Santa Catarina. This is the second Adenomera species endemic to the Atlantic Forest of eastern Santa Catarina in southern Brazil, sympatric to Adenomera engelsi and allopatric to the sibling A. araucaria.